Accumulation of Hg, Pb, Cr, and Fe in muscle and head of four fish species: Diplodus annularis, Zosterisessor ophiocephalus, Liza aurata and Caranx rhonchus - Rebah, Faouzi Ben (JOURNAL OF ADVANCES IN BIOLOGY, 2014)
Because heavy metal pollution was recently reported in the Gulf of Gabes (Tunisia), the concentration of selected elements (Hg, Pb, Cr and Fe) in the muscles and heads for fish species, Diplodus annularis, Zosterisessor ophiocephalus, Liza aurata and Caranx rhonchus, were determined using atomic absorption spectrometry. The element contents were identified to have the following decreasing sequence: Fe > Pb, Cr > Hg in both muscles and heads. However, levels of these elements were higher in heads but in trace in muscles. This indicates that, heads were contaminated but muscles were safe for the species caught from Gabes gulf area.